Estudio de prefactibilidad para la operatividad de un centro de capacitación microempresarial en el sector norte del cantón Durán - Pintado Barros, Jonhatan Walter (2019)
The present economic study analyzed the feasibility of creating a training center in the northern sector of the Duran Canton, to provide tools, share knowledge, develop a human group, prepare them to make their businesses progress and become sources of income that allow to improve the quality of life of both the microentrepreneur and their employees. The general objective was to design a feasibility study to determine the creation of a micro business training center in the northern sector of the Durán canton. The methodology used was exploratory, with theoretical and practical research, as well as interviews with microentrepreneurs………